The Correlation of Wealth Between Parents and Children in Australia. (24th February 2022) - Siminski, Peter; Yu, Sin Hung (Timothy)
Abstract: We present the first estimates of intergenerational wealth mobility for Australia. The rank correlation is 0.253, compared to 0.306 for the United States using comparable methods. This correlation varies greatly by child age when wealth is observed, from 0.1 before age 30, to 0.5 after age 40. This sharp increase with age is stronger than for other countries, is not explained by sample selection bias and is not specific to particular types of wealth. We also argue that neither income mobility nor wealth mobility, as operationalised in empirical work, align neatly with the wealth concept in the Becker & Tomes framework.